2022
DOI: 10.1039/d1cp04128b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of packing arrangement on the optical properties of C60 cluster aggregates

Abstract: Excitons in cube–like and chain–like C60 cluster aggregates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…In particular, C 60 shows a series of optical absorption features in multilayer and other aggregated structures 23 , where different spectroscopy studies have indicated that these optical transitions correspond to the formation of excitons with differing charge-transfer character 24 28 . Although these indirect results are supported by time-dependent density functional theory calculations 29 31 , quantitative access to the multiorbital wavefunction contributions (see Eq. ( 1 ) and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, C 60 shows a series of optical absorption features in multilayer and other aggregated structures 23 , where different spectroscopy studies have indicated that these optical transitions correspond to the formation of excitons with differing charge-transfer character 24 28 . Although these indirect results are supported by time-dependent density functional theory calculations 29 31 , quantitative access to the multiorbital wavefunction contributions (see Eq. ( 1 ) and Fig.…”
Section: Resultsmentioning
confidence: 99%